Processing methods for enrichment of diatoms in sediment samples - Thanh, Tran Duc (Vietnam Journal of Earth Sciences, 2015)
Based on the existing guide-documentation and practical experiences of author, the paper presents the processing methods for enrichment of diatoms in sediment samples for classification and research in biostratigraphy. Processing samples must be performed by five stages as: 1. sample preparation; 2. cleaning and preliminary enrichment; 3- enrichment by heavy solution; 4. creating hard specimen; 5.recovering and recycling heavy solution. Depending on the kind of processed samples, the operations need to be adjusted accordingly. For the stage of enrichment by heavy solution, the result is influenced greatly by all three factors such as: density of solution, centrifugal speed and time. Under the condition of humid climate, the preliminary enriched samples are difficult to keep dry absolutely. Therefore, the standard solution density of 2.6 prepared from the proportional weight: H2O: CdI2: KI = 1: 2.5: 2.25 may be reduced slightly when mixed with the samples for centrifugation. For this reason, it needs to make the appropriate adjustments conditions such as: increasing heavy solution density or decreasing centrifugal speed. Recovering and recycling heavy solution are particularly necessary, and the recovery rate can reach up 75-80%. The formulas given in this article could make recycling heavy solution fast and accurately. References Đào Thị Miên, Nguyễn Ngọc, Nguyễn Thị Thu Cúc, 2006: Ý nghĩa của các phức hệ Diatomeae trong việc xác định nguồn gốc trầm tích cuối Holocen giữa - Holocen muộn ở một số đồng bằng ven biển Việt Nam. Tạp chí Địa chất, số 295 (7-8), tr.1-14. Juse, A.P.; Proschkina-Laverenko, A.I.; Sheshykova, V.C., 1949: Phân tích tảo Silics (Diatoms). Tập I. Địa chất. Nhà xuất bản Văn liệu Quốc gia. Leningrad, 339tr (tiếng Nga). Juze A.P., 1963: Ngành Bacillariophyta, tảo Diatomeae. Trong: “Cơ sở cổ sinh”. T.15. Nhà xuất bản Viện Hàn lâm Khoa học Liên Xô, Mascơva (tiếng Nga). Đặng Đức Nga, Trần Đức Thạnh, 1982: Các phức hệ tảo Silic (Diatomeae) Pliocen Tây Nguyên và ý nghĩa của chúng. Tạp chí Các Khoa học về Trái Đất. T.4, 1, tr.27-30. Tạ Thị kim Oanh, Nguyễn Văn Lập, 2000: Diatom - chỉ thị môi trường trầm tích và dao động mực nước biển trong Pleistocen muộn- Holocen. Tạp chí Các Khoa học về Trái Đất, T.22, 3, tr.226-233. Trần Đức Thạnh, 1991: Phân bố của tảo silic trong trầm tích bề mặt vùng ven biển từ cửa Văn Úc tới cửa Ba Lạt. Tuyển tập Tài nguyên và Môi trường biển. Tập I. Nxb. Khoa học và Kỹ thuật, Hà Nội, tr.67-72.